Digital technologies: drivers of economic growth during COVID-19 pandemic - S. G. Serikov (Вестник университета)
The article examines the drivers of economic growth in a difficult epidemiological situation. The problems of economic activity during this period are identified. It was revealed that cloud technologies, digital platforms and blockchain technologies can act as the main drivers of the growth of the pandemic economy. A comparative analysis of the level of development of digitalization processes in the Russian economy in comparison with other countries is presented. The main problems and threats to the development of the digitalization process in Russia are noted. It has been established that the digital economy in Russia is in its infancy – the main direction is the acquisition of equipment (computer and communication technology). Despite the measures taken by the state to launch digitalization processes in the domestic economy, Russian companies lag far behind foreign competitors in terms of the degree of implementation and use of digital technologies in their activities. In the current situation, it is necessary to continue state support for such areas as import substitution, the export of domestic digital products, and the creation of equal operating conditions for all IT companies.